2019
DOI: 10.1161/strokeaha.118.023553
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Stroke

Abstract: Stroke is the leading cause of serious long-term disability in the US, leaving less than half of survivors able to return directly home. 1 Stroke recurrence, estimated as high as 17% over 5 years, also remains unacceptably high. 1 The use of lytic drugs and endovascular devices have revolutionized the care of select stroke patients in the acute setting. However, enormous challenges remain in changing the trajectory of stroke recovery for the vast majority of patients who do not qualify or remain disabled after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 49 publications
4
72
0
4
Order By: Relevance
“…Continuous positive airway pressure (CPAP) is the first choice for OSA treatment [ 68 ]. There are different reports on the outcomes of CPAP treatment on OSA.…”
Section: Treatment Of Bsds In Strokementioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is the first choice for OSA treatment [ 68 ]. There are different reports on the outcomes of CPAP treatment on OSA.…”
Section: Treatment Of Bsds In Strokementioning
confidence: 99%
“…Moderate-to-severe OSA was found to significantly increase cardiovascular risk, especially the risk of fatal or nonfatal stroke (relative risk, 2.02; 95% confidence interval 1.4-2.9) in a meta-analysis study 2 . Additionally, OSA has a negative effect on stroke outcome by worsening functional recovery and increasing the risk of recurrent stroke and mortality 3 which is improved by proper treatment of OSA 4 . The most effective treatment for OSA is continuous positive airway pressure (CPAP).…”
mentioning
confidence: 99%
“…The patients recruited in their study were all men with a relatively young age (56.8 ± 10.7 y/o) and mild stroke severity (HIHSS, 4 ± 4.3). In addition, central sleep apnea (CSA), which is usually noted in patients with acute stroke with unclear clinical significance and improve over time 3 , was not excluded in their study. Therefore, their results cannot be generalized to more severe stroke patients with OSA.…”
mentioning
confidence: 99%
“…[ 12 , 13 ] For patients with stroke, insomnia not only aggravates the physical symptoms, seriously affects the prognosis and quality of life, but may also lead to negative emotions such as anxiety and depression, trigger mental disorders, accelerate the decline of cognitive function, and even cause the recurrence of stroke, thus increasing the economic burden of families and society. [ 14 , 15 ] Medication and cognitive behavioral therapy are mainly adopted for patients with insomnia after stroke at present. However, studies have shown that long-term use of benzodiazepines and other similar drugs will lead to drug dependence, drowsiness, vertigo, cognitive impairment, and other side effects.…”
Section: Introductionmentioning
confidence: 99%